Filmes közéletben betöltött szerepének dokumentációja
The collection includes records of Schiffer's activities as a prominent public figure, and activist in the civil society. Besides being a social documentary filmmaker he fulfilled important positions in film professional and civil organizations, such as "Alliance of Hungarian Film Clubs" (Magyar Filmklubok Szövetsége); "Club for Transparency" (Nyilvánosság Klub); "Film Fund for Hungarian Historical Documentaries" (Magyar Történelmi Filmalapítvány). The collection offers an insight into the of the regime change and the cultural and political sphere of Hungary after 1989. Accruals not expected